2008
DOI: 10.1016/j.tox.2008.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Hexavalent chromium causes the oxidation of thioredoxin in human bronchial epithelial cells

Abstract: Hexavalent chromium [Cr(VI)] species such as chromates are cytotoxic. Inhalational exposure is a primary concern in many Cr-related industries and their immediate environments, and bronchial epithelial cells are directly exposed to inhaled Cr(VI). Chromates are readily taken up by cells and are reduced to reactive Cr species which may also result in the generation of reactive oxygen species (ROS). The thioredoxin (Trx) system has a key role in the maintenance of cellular thiol redox balance and is essential fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
66
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(70 citation statements)
references
References 63 publications
4
66
0
Order By: Relevance
“…12 Trace elements, including the essential and the toxic, play an important role in the life and environmental sciences; one of them is chromium (Cr). 13 Chromium is an important transition metal ion with diverse industrial applications and is an essential micronutrient required to promote the action of insulin in body tissues so that the body can use sugars, proteins and fats. 14 Two of the most important oxidation states of chromium are Cr (III) and Cr (VI).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…12 Trace elements, including the essential and the toxic, play an important role in the life and environmental sciences; one of them is chromium (Cr). 13 Chromium is an important transition metal ion with diverse industrial applications and is an essential micronutrient required to promote the action of insulin in body tissues so that the body can use sugars, proteins and fats. 14 Two of the most important oxidation states of chromium are Cr (III) and Cr (VI).…”
Section: Introductionmentioning
confidence: 99%
“…Cr 6+ has been shown to be carcinogenic and mutagenic to biological system. 13,14 On the contrary, Cr 3+ salts such as chromium polynicotinate, chromium chloride and chromium picolinate are used as micronutrients and nutritional supplements and have been demonstrated to exhibit a significant number of health benefits in animals and human. 16 The Cr deficiency includes symptoms resembling diabetes, such as glucose intolerance impairment with the requirement of increasing insulin, etc, and Cr supplement can alleviate these symptoms.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In many occupations, workers handling chromium(VI)-containing products are at the risk of lung cancer, dermatitis, and gastrointestinal ulcers (1,2). Hexavalent chromium is transported into the cell via non-specifi c anion transport systems (3,4), where it converts to trivalent chromium (Cr III ), whose highest levels have been reported in the kidney, liver, spleen, and bones (5). Although cytotoxic mechanisms are not exactly understood, several studies have showed that Cr VI induces oxidative stress, DNA damage, single-and double-strand breaks, and affects survival signalling pathways (6)(7)(8).…”
mentioning
confidence: 99%